Review paperKeloids: current prophylactic and therapeutic methods - Bienias, Wojciech; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Prophylaxis and therapy of keloids present a big challenge for medicine, despite the increasing knowledge about their pathogenesis. There are a lot of therapeutic methods but their effectiveness is still limited and unsatisfactory. These methods are divided into surgical, pharmacological and physical ones as well as the most frequently applied combined therapy, which is the most effective one. A surgical way of removing keloids is becoming less common and the method of intralesional application of steroids still remains the treatment of choice. In addition to the above there are cryotherapy, laser therapy, pressure therapy, X-ray irradiation and silicone products in a form of gels and dressings. Relatively new methods are intralesional injections of verapamil and 5-fluorouracil. Enalapril and troglitazone, which are currently used in the treatment of hypertension and diabetes, are expected to be of use as well. Biological drugs like monoclonal antibodies against tumor growth factor (TGF)-β1, TGF-β2 and vascular endothelial growth factor and analogues of TGF-β3 are also potential solutions in the treatment of keloids. Further studies on the treatment of keloids should result in more efficient therapies.